The effect of early everolimus administration on the renal function while reducing the dosage of calcineurin inhibitors in liver transplant recipients in a long-term follow-up - V. E. Syutkin; A. A. Salienko; O. D. Olisov; S. V. Zhuravel; M. S. Novruzbekov (Трансплантология (Москва), 2021)
Introduction. The lifelong use of calcineurin inhibitors in liver transplant recipients leads to an increased incidence of chronic kidney disease.Objective. To compare the changes in glomerular filtration rate over five years in liver transplant recipients between those on everolimus with a reduced exposure to calcineurin inhibitors and those on standard doses of calcineurin inhibitors.Material and methods. Fourteen liver transplant recipient switched to everolimus with a minimization of calcineurin inhibitors exposure in the first months after liver transplantation from February 2009 to February 2015 who had received that therapy continuously for at least 60 months were included in the case-control study. Twenty eight liver transplant recipients (matched by sex, etiology of the underlying disease, calcineurin inhibitors) who were followed-up for at least 60 months after liver transplantation, who had received no dose of everolimus, in whom the glomerular filtration rate could be calculated at all points of analysis were selected as a comparison group (1:2). Glomerular filtration rate was calculated immediately before liver transplantation; 12, 24, 36, 48, and 60 months after liver transplantation. The glomerular filtration rate after liver transplantation was also calculated for liver transplant recipients from the main group immediately before the conversion to everolimus.Results. Before liver transplantation, the median of glomerular filtration rate in the main group of liver transplant recipients was lower (81.2 ml/min) than in the comparison group (97.5 ml/min, p=0.01). After liver transplantation, the renal function worsened in both groups of patients. In a pairwise comparison, the medians of glomerular filtration rate were statistically significantly lower after 12 months, 24 months, 36 months, 48 months after liver transplantation, than before liver transplantation. The median of glomerular filtration rate at the time of immunosuppression conversion was 44.3 ml/min. After the conversion of immunosuppression, the median of glomerular filtration rate gradually increased, and after 36 months the differences in glomerular filtration rate reached statistical significance compared with the level before conversion (69.4 ml/min;p=0.048). These differences still increased after 60 months after conversion (72.3 ml/min; p=0.041).Conclusion. Long-term administration of everolimus with minimization of calcineurin inhibitors exposure with the early conversion to this immunosuppression regime provides a steady improvement in renal function in liver transplant recipients with a low glomerular filtration rate in the preoperative and early post-transplant period.